Future Scenarios work in Cambodia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Key policy-makers and stakeholders from variety of sectors came together at the end of October in 2014 in Phnom Phen, Cambodia for a second workshop that focused on scenario-guided policy analysis on the future of development, food security and the environment under climate change in Southeast Asia. The workshop was organized by UNEP-WCMC, and CCAFS and is part of UNEP_WCMC's project "Commodities and Biodiversity - Planning for Future Capacity' funded by The John D. & Catherine T MacArthur Foundation.